2008
DOI: 10.1097/iae.0b013e318165767e
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Triamcinolone for Diabetic Macular Edema

Abstract: Regarding eyes with refractory diffuse DME with cystic changes, 4 mg IVTA does not appear to be more effective than 1 or 2 mg IVTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
1
32
0
2
Order By: Relevance
“…The greatest improvement in BCVA at 12 months was in the 0.3 mg group (11.8 letter gain) compared to the 0.5 mg group (8.8 letter gain) or sham injection (1.4 letter loss). In this study, rescue laser was 114 Single dose Jonas et al 115 Single dose Joussen et al 116 Study protocol Avci and Kaderli 117 Anaesthetic technique Kang et al 118 Single dose Kim et al 119 Single injection and CME Lam et al 120 Single injection Lee 121 Single injection Maia et al 122 Single dose Massin et al 123 Single dose Mohamed et al 124 Post hoc analysis Nakamura et al 125 Single dose Spandau et al 126 Single dose Tunc 127 <6 months Verma et al 128 Single 13 Current treatments in diabetic macular oedema Current treatments in diabetic macular oedema 23 Current treatments in diabetic macular oedema Adverse events are shown in tables 9 and 16. Conjunctival haemorrhages were higher in the ranibizumab arms compared with laser (RESTORE) or no treatment (RESOLVE).…”
Section: Ranibizumabmentioning
confidence: 92%
“…The greatest improvement in BCVA at 12 months was in the 0.3 mg group (11.8 letter gain) compared to the 0.5 mg group (8.8 letter gain) or sham injection (1.4 letter loss). In this study, rescue laser was 114 Single dose Jonas et al 115 Single dose Joussen et al 116 Study protocol Avci and Kaderli 117 Anaesthetic technique Kang et al 118 Single dose Kim et al 119 Single injection and CME Lam et al 120 Single injection Lee 121 Single injection Maia et al 122 Single dose Massin et al 123 Single dose Mohamed et al 124 Post hoc analysis Nakamura et al 125 Single dose Spandau et al 126 Single dose Tunc 127 <6 months Verma et al 128 Single 13 Current treatments in diabetic macular oedema Current treatments in diabetic macular oedema 23 Current treatments in diabetic macular oedema Adverse events are shown in tables 9 and 16. Conjunctival haemorrhages were higher in the ranibizumab arms compared with laser (RESTORE) or no treatment (RESOLVE).…”
Section: Ranibizumabmentioning
confidence: 92%
“…Both Hauser et al [239] and Audren et al [240] showed that the use of the higher 4-mg dose of IVTA does not have enough advantages over the lower 1- or 2-mg dose. However, Lam et al [241] published a comparison between 4- and 8-mg doses and showed that the higher dose had a more sustained effect on both visual acuity and central macular thickness although with a trend to more ocular hypertensive responses.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
“…IVTA was shown to significantly improve visual acuity, foveal thickness, macular function, macular thickness, and retinal arteriolar and venular diameter in patients with DME [11][12][13]. A recently published 2-year multicenter trial in patients with DME demonstrated that preservative-free IVTA (1 or 4 mg) was inferior to focal/grid photocoagulation in preventing visual acuity loss and was associated with a higher incidence of IOP elevation [2 ].…”
Section: Triamcinolone Acetonidementioning
confidence: 99%